PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING PADA PESERTA DIDIK DI SD NEGERI CIAWIGEDE - Aryani, Wiwik Dyah; Saadah, Neng Siti Nur; Anggraeni, Reni; Alamri, Sazili Mustofa; Setiawan, Rudi; Ihsan, Muhammad Nur (Penerbit Widina, Widina Media Utama, 2025)
This study aims to apply the Discovery Learning model to students of Ciawigede Elementary School to improve problem-solving skills in Islamic Religious Education learning. The method used is classroom action research with a qualitative descriptive approach using two cycles, where each cycle consists of planning, implementation, observation, and reflection. The results of the study showed a significant increase in students' problem-solving skills before and after the application of this learning model. The average student score increased from 74.3 in cycle I to 79.6 in cycle II, with the percentage of classical learning completion increasing from 86% to 89.66%. This study concludes that the Discovery Learning model is effective in improving student activity and learning outcomes, as well as encouraging students to be more active and creative in the learning process.ABSTRAKPenelitian ini bertujuan untuk menerapkan model pembelajaran Discovery Learning pada siswa SD Negeri Ciawigede untuk meningkatkan kemampuan pemecahan masalah dalam pembelajaran PAI. Metode yang digunakan adalah penelitian tindakan kelas dengan pendekatan deskriptif kualitatif menggunakan dua siklus, di mana setiap siklus terdiri dari perencanaan, pelaksanaan, pengamatan, dan refleksi. Hasil penelitian menunjukkan adanya peningkatan yang signifikan dalam kemampuan pemecahan masalah siswa sebelum dan setelah penerapan model pembelajaran ini. Rata-rata nilai siswa meningkat dari 74,3 pada siklus I menjadi 79,6 pada siklus II, dengan persentase ketuntasan belajar klasikal meningkat dari 86% menjadi 89,66%. Penelitian ini menyimpulkan bahwa model Discovery Learning efektif dalam meningkatkan aktivitas dan hasil belajar siswa, serta mendorong siswa untuk lebih aktif dan kreatif dalam proses pembelajaran.